Investigation on the effect of telomerase downregulation on transcriptome of HCT116 human colon carcinoma cells / Muhammad Zuhair Mohd Zain - Muhammad Zuhair , Mohd Zain (2021)
Telomerase is a ribonucleoprotein complex that adds TTAGGG tandem repeats to the 3’ end of the telomere facilitating cellular immortalization and tumorigenesis. The reverse transcriptase activity of telomerase is mainly due to its human telomerase reverse transcriptase (hTERT) subunits. Telomerase was found to be highly expressed in diverse cancer types of cancerous cells but remains silence in normal somatic cells making telomerase a viable therapeutic target in cancer treatment. In order to investigate the roles of hTERT downregulation in relation to global RNA expression, colorectal cancer cell lines HCT116 were transfected with short interference RNA (siRNA) targeting hTERT before being subjected to transcriptomic analysis using RNA sequencing (RNA-seq) technology. Transfection of TERT siRNA induced downregulation of hTERT at mRNA and protein level. Transcriptomic results revealed intricate transcriptomic responses arising from TERT siRNA transfection. 474 genes were identified to be present in both control and TERT-siRNA-transfected, with only 50 genes were identified as significantly differentially expressed genes (DEG). From 50 genes, 21 genes were upregulated and 29 genes were downregulated. According to Database for Annotation, Visualization and Integrated Discovery (DAVID), transfection of TERT siRNA induced changes of genes related to apoptotic process, transcription, post-translational modification, and signal transduction. TERT siRNA transfection has triggered downregulation of genes related to apoptosis. This is consistent with changes of genes related to transcription, post-translational modification, and signal transduction that is likely linked to cellular growth, proliferation, and progression. The changes in RNA marker suggested hTERT may play crucial role in regulating apoptosis and cellular proliferation.